Location of monovalent cation binding sites in the gramicidin channel. - Urry, D W (1982)
Six syntheses of gramicidin A have been carried out, each with 90% 13 C enrichment of a single carbonyl carbon these being the formyl, Val-1, Trp-9, Trp-11, Trp-13, and Trp-15 carbonyl carbons. Each gramicidin A was incorporated as the channel state into phospholipid structures, and the chemical shift of the carbonyl carbon resonance was monitored by 13C NMR as a function of ion concentration. Plots of Na+- and Tl+-induced chemical shifts as a function of carbonyl location in the channel indicate two symmetrically related binding sites centered at the tryptophan carbonyls and separated by 23 A. The absence of ion-induced chemical shifts for the formyl and Val-1 carbonyl carbon resonances indicates that there is no binding site midway through the channel but rather a central free-energy barrier for ion transit through the channel. Ion induced chemical shifts of the tryptophan carbonyl carbon resonances at 100 mM Na+ verify that the tight binding constant (Kbt congruent to 70 M-1), observed with 23Na NMR, results from binding within the channel. This observation and the lateral, triangular distribution of the coordinating Trp-9, -11, and -13 carbonyls combine to provide an experimental demonstration that the carbonyls of the walls of the channel directly coordinate the ion, successfully competing with the polar solvent. With the binding sites verified and localized, it is possible to conclude that the transport mechanism for Na+ is well represented by the case of the two-site model [D. W. Urry, Venkatachalam, C. M., Spisni, A., Läuger, P. & Khaled, M. A. (1980) Proc. Natl. Acad. Sci. USA 77, 2028--2032].